2018
DOI: 10.3389/fmars.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries Exploitation by Albatross Quantified With Lipid Analysis

Abstract: Mortality from incidental bycatch in longline fishery operations is a global threat to seabird populations, and especially so for the albatross family (Diomedeidae) in which 15 out of 22 species are threatened with extinction. Despite the risks, fisheries remain attractive to many species of seabird by providing access to high-energy foods in the form of discarded fish and offal, target fish, and baited hooks. Current policy regarding fisheries management is increasingly aimed at discard reform, exemplified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 73 publications
(93 reference statements)
0
19
0
1
Order By: Relevance
“…Elephant seals use suction feeding to consume prey whole, so we homogenized each whole prey item separately, then combined mass-specific aliquots from each individual into a species-homogenate (n = 3-15 individuals/homogenate). Three to five 1.5 g subsamples (replicates) were taken from each preyhomogenate, except when there was a single representative individual (Conners et al, 2018). Using a prey-homogenate gives an average prey FA profile but eliminates data on within-species variation between individuals in FA composition; however, within-species variability is likely small compared to betweenspecies variation (Budge et al, 2002).…”
Section: Lipid Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elephant seals use suction feeding to consume prey whole, so we homogenized each whole prey item separately, then combined mass-specific aliquots from each individual into a species-homogenate (n = 3-15 individuals/homogenate). Three to five 1.5 g subsamples (replicates) were taken from each preyhomogenate, except when there was a single representative individual (Conners et al, 2018). Using a prey-homogenate gives an average prey FA profile but eliminates data on within-species variation between individuals in FA composition; however, within-species variability is likely small compared to betweenspecies variation (Budge et al, 2002).…”
Section: Lipid Extractionmentioning
confidence: 99%
“…NMDS ordination allowed us to see the relations of prey species in FA space, and, importantly, showed distinct separation between fish and squid FA profiles. Squids can be problematic in QFASA models (Conners et al, 2018), because most of their lipids are found in the large digestive gland, rather than other tissues like the mantle (Phillips et al, 2002). This results in a FA profile that may strongly resemble that of recently consumed prey present in the digestive gland.…”
Section: Evaluating Qfasamentioning
confidence: 99%
See 2 more Smart Citations
“…glass and flying squid), as well as fish (e.g. lanternfish -Myctophidae -and flying fish), crustaceans, and fish eggs (Harrison et al 1983, Bisson 2008, Conners et al 2018. Despite the ecological differences between them, both the endangered Newell's shearwater and the abundant Laysan albatross have experienced trophic declines within the past century (Morra et al 2019).…”
Section: Introductionmentioning
confidence: 99%